"In vitro" effect of fungicides on mycelial growth of bipolaris maydis - Yamashita, O. M.; Kobayashi, L.; Cassetari Neto, D.; Santi, A.; Peres, W. M.; Carvalho, M. A. C.; Kappes, C. (Scientia Agraria Paranaensis, 2000)
Leaf spot is a disease provoked by the fungus Bipolaris maydis, that it causes great damages for annual crops, as the corn, the wheat and the oats. Tests "in vitro" were accomplished seeking to evaluate the efficiency in the inhibition of the mycelial growth of that patogenic fungus through five fungicides: tetraconazol, tebuconazole, azoxystrobin + cyproconazole, trifloxystrobin + ropiconazole and trifloxystrobin + cyproconazole were ested fungicides. For the determination of the efficiency f the products, the daily growth of the fungus was valuated, being compared with the control. It was determined the percentage of growth inhibition. All of the treatments were effective in the inhibition of the growth of this fungus.